Study on the Design and Development of Advanced Inorganic Polymers for Thermal Energy Storage (TES) Systems - Ioanna Giannopoulou; Loizos Georgiou; Konstantina Oikonomopoulou; Maria Spanou; Alexandros Michaelides; Demetris Nicolaides (Energies)
Thermal Energy Storage (TES) technologies improve solar power dispatchability by addressing the important challenge of energy intermittency. Sensible heat energy storage technology using materials based on Ordinary Portland Cement (OPC) is the simplest and most economical. However, the operation of these materials is limited to temperatures below 400 °C due to the structural degradation of OPC at this temperature. This paper investigates the design and development of inorganic polymers based on Construction and Demolition Waste (CDW) as a sustainable, low-cost, and environmentally friendly alternative to OPC-based materials for high-temperature sensible TES applications. Based on the ternary systems Na2O-SiO2-Al2O3 and K2O-SiO2-Al2O3, representative compositions of CDW-based inorganic polymers were theoretically designed and evaluated using the thermochemical software FactSage 7.0. The experimental verification of the theoretically designed inorganic polymers confirmed that they can withstand temperatures higher than 500 and up to 700 °C. The optimized materials developed compressive strength around 20 MPa, which was improved with temperatures up to 500 °C and then decreased. Moreover, they presented thermal capacities from 600 to 1090 J kg−1 °C −1, thermal diffusivity in the range of 4.7–5.6 × 10−7 m2 s−1, and thermal conductivity from 0.6 to 1 W m−1 °C−1. These properties render the developed inorganic polymers significant candidates for TES applications.